Yours, Mine, and Ours: A Qualitative Analysis of the Impact of Type 1 Diabetes Management in Older Adult Married Couples - Litchman, Michelle L. (Diabetes Spectr, 2019)
OBJECTIVE. The purpose of this study was to understand perceptions of diabetes management responsibilities and the impact of diabetes on day-to-day activities in older adulthood for individuals with type 1 diabetes and their spouses. DESIGN AND METHODS. This qualitative content analysis used a constant-compare approach to analyze individual interviews conducted with older adults and their spouses. People with type 1 diabetes (PWD) and their spouses were interviewed regarding how they coped or dealt with diabetes, what activities they carried out or avoided because of diabetes, and how they appraised diabetes as an individual or shared problem. RESULTS. Participants (n = 52) included 26 older adults with diabetes (mean age 69 years, SD 2.56 years; 38.5% female) and their spouses (mean age 68 years, SD 5.11 years; 61.5% female). Half of the PWD (50%) and the majority of spouses (76.9%) appraised diabetes as a shared issue. Five themes emerged from the interview data: 1) Perceptions pf PWD of spouse involvement in diabetes care, 2) PWD underestimated the impact of diabetes on their spouse’s daily lives, 3) gendered nature of spouses supporting diabetes management, 4) evolution of diabetes and the relationship across developmental time, and 5) differences in diabetes management among couples. CONCLUSION. Older adults with type 1 diabetes and their spouses have different perspectives regarding diabetes support and responsibility and may not always realize what support is being provided or needed to optimize effective diabetes management. Advancing age with or without diabetes complications may necessitate that spouses provide diabetes support. Diabetes management training for spouses would likely be helpful.